Fibrilación auricular en el postoperatorio de cirugía cardiaca: factores de riesgo y morbimortalidad - Cereceda B., Mauricio; Solanes, Federica; Suárez H., Luisa; Vildoso C., Juan Pablo; Tamblay V., José A.; Zamorano G., Jaime (Revista Hospital Clínico Universidad de Chile, 2008)
Introduction: postoperative atrial fibrillation (POAF) is the most frequent arrhythmia observed in patients undergoing a cardiac surgery. The worldwide incidence is 30 to 65% of cardiac surgery procedures, and is more frequent in patients undergoing a cardiac valve surgery. This arrhyhtmia implies an increment in the lenght and in the total costs of hospitalization, and is associated with serious adverse events like stroke, bleeding and death. The aim of this study was to know the incidence, risk factors, morbidity and mortality associated with POAF in our institution during one year. Main results: we analyze 321 patients that undergone a cardiac surgery during 2003. The incidence of POAF was 6,7% and the risk factors associated were the use of cold crystalloid cardioplegia (p < 0,05) and dyslipidemia (p < 0,05). Also, the left ventricle end diastolic diameter was larger but not significant (p = 0,053) in patients with POAF in comparison with patients without POAF. POAF results in an increment of the costs and the lenght of hospitalization. There was no mortality attributed to this arrhythmia in our patients. Conclusion: in this retrospective analysis of patients undergoing cardiac surgery there was a lower incidence of POAF in comparison with other series. The risk factors in this population of patients were the use of cold crystalloid cardioplegia and dyslipidemia. Although this arrhythmia was associated with more days of hospitalization, there were no difference in mortality between patients with POAF and patients without POAF.